Stage Actors and Modern Acting Methods Move to Hollywood in the 1930s - Baron, Cynthia (Cinémas, 2014)
In this article, the author considers factors in commercial 1930s American theatre and film which led to the unusual circumstance of many stage-trained actors employing ostensibly theatrical acting methods to respond effectively to the challenges and opportunities of industrial sound film production. The author proposes that with American sound cinema fundamentally changing employment prospects on Broadway and Hollywood production practices, the 1930s represent a unique moment in the history of American performing arts, wherein stage-trained actors in New York and Hollywood developed performances according to principles of modern acting articulated by Stanislavsky, the American Academy of Dramatic Arts in New York and the acting manuals written by theatre-trained professionals and used by both stage and screen actors. To illustrate certain aspects of the era’s conception of modern acting, the author analyzes a scene from Captains Courageous (Victor Flemining, 1937) with Spencer Tracy and a scene from The Guardsman (Sidney Franklin, 1931) with Alfred Lunt and Lynn Fontanne.